USING OF PR-TECHNOLOGIES IN PRACTICE OF SCIENTIFIC LIBRARY IN NATIONAL UNIVERSITY OF WATER MANAGEMENT AND NATURE RESOURCES USE - Perelehina, Valentyna; Ponarina, Iryna Yo. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In this article PR-technologies which are used in scientific library are disclosed. Appropriate examples are presented, acquired experience is analyzed and prospects of development are disclosed.